New steps on an old path: Novel estrogen receptor inhibitors in breast cancer. (December 2022) - Pagliuca, Martina; Donato, Marco; D'Amato, Agostina Lagodin; Rosanova, Mario; Russo, Anna Orsola Maria; Scafetta, Roberta; De Angelis, Carmine; Trivedi, Meghna V.; André, Fabrice; Arpino, Grazia; Del Mastro, Lucia; De Laurentiis, Michelino; et al.
Abstract: Estrogen receptor (ER) signaling represents the main driver of tumor growth and survival in hormone receptor positive (HR+) breast cancer (BC). Thus, endocrine therapy (ET) alone or in combination with targeted agents constitutes the mainstay of the treatment for this BC subtype. Despite its efficacy, intrinsic or acquired resistance to ET occurs in a large proportion of cases, mainly due to aberrant activation of ER signaling (i.e. through ligand-independent ER activation, in the presence of estrogen receptor 1 ( ESR1) gene aberration or ER protein phosphorylation) and/or the upregulation of escape pathways, such as the PI3K/AKT/mTOR pathway. Therefore, the development of new ER pathway targeting agents remains essential to delay and overcome ET resistance, enhance treatment efficacy and tolerability, and ultimately prolong patient survival and improve their quality of life. Several novel ER targeting agents are currently under investigation. Among these, the oral selective ER degraders (SERDs) represent the pharmacological class at the most advanced stage of development and promise to enrich the therapeutic armamentarium of HR+ BC in the next few years, as they showed promising results in several clinical trials, either as single ET agents or in combination with targeted therapies. In this manuscript, we aim to provide a comprehensive overview on the clinical development of novel ER targeting agents, reporting the most up-to-date evidence on oral SERDs and other compounds, including new selective ER modulators (SERMs), ER proteolysis targeting chimera (PROTACs), selective ER covalent antagonists (SERCAs), complete ER antagonists (CERANs), selective human ER partial agonists (ShERPAs). Furthermore, we discuss the potential implications of introducing these novel treatment strategies in the evolving and complex therapeutic scenario of HR+ BC. Graphical Abstract: ga1 Highlights: Hormone receptor positive breast cancer has an evolving therapeutic scenario. Estrogen receptor is the main driver of tumor growth for this breast cancer subtype. The mainstay of the treatment is represented by endocrine therapy. The development of endocrine resistance represents a critical challenge. Novel estrogen receptor signalling inhibitors are currently under development.